Antibiotic-induced dysbiosis in the SCIME™ recapitulates microbial community diversity and metabolites modulation of in vivo disease - Dalle Vedove, Elena; Benvenga, Alessia; Nicolai, Gianluca; Massimini, Marcella; Giordano, Maria Veronica; Di Pierro, Francesco; Bachetti, Benedetta (Frontiers in Microbiology, 2024)
Establishing the context Intestinal dysbiosis is a significant concern among dog owners, and the gut health of pets is an emerging research field. In this context, the Simulator of the Canine Intestinal Microbial Ecosystem (SCIME™) was recently developed and validated with in vivo data. Stating the purpose/introducing the study The current study presents a further application of this model by using amoxicillin and clavulanic acid to induce dysbiosis, aiming to provoke changes in microbial community and metabolite production, which are well-known markers of the disease in vivo. Describing methodology Following the induction of dysbiosis, prebiotic supplementation was tested to investigate the potential for microbiota recovery under different dietary conditions. Presenting the results The results showed that antibiotic stimulation in the SCIME™ model can produce significant changes in microbial communities and metabolic activity, including a decrease in microbial richness, a reduction in propionic acid production, and alterations in microbial composition. Additionally, changes in ammonium and butyric acid levels induced by the tested diets were observed. Discussing the findings This alteration in microbial community and metabolites production mimicks in vivo canine dysbiosis patterns. A novel dynamic in vitro model simulating canine antibiotic-induced dysbiosis, capable of reproducing microbial and metabolic changes observed in vivo, has been developed and is suitable for testing the effects of nutritional changes.